A note on the biogeographical origin of the brine shrimp Artemia urmiana Günther, 1899 from Urmia Lake, Iran - Eimanifar, Amin; Asem, Alireza; Djamali, Morteza; Wink, Michael (Zootaxa, 2016)
The brine shrimp Artemia urmiana, an abundant inhabitant of the hypersaline Urmia Lake in northwestern Iran, has recently been described from Lake Koyashskoe, also a shallow hypersaline lake that is located on the Black Sea coast of the Crimean Peninsula (Ukraine). This discovery has questioned the endemicity of A. urmiana in Urmia Lake and has also brought into question the biogeographical origin of this species. In the present study, we combined recent genetic divergence data (mtDNA-COI) with palaeoecological evidence to address the biogeographical origin of A. urmiana. Calibration of the molecular clock of the COI region was set by assigning the age of the micro-crustacean Daphnia pulex minimally at 145 Mya. The divergence age of A. urmiana in Urmia Lake dates back to 383,000 years, whereas Ukrainian Artemia reflects a very young populations that diverged about 196,000 years ago. Palaeoecological evidence suggests that the age of the major habitat of A. urmiana i.e. Urmia Lake goes back to the Tertiary Period while the Ukranian habitats of the species are very young, by virtue of geological features of the Holocene age. We conclude that the biogeographical origin of A. urmiana is outside of Europe and the current state of knowledge strongly suggests that Urmia Lake has been the major source of its expansion into its modern habitats in Europe.